IS THE LOYALTY PROGRAM EFFECTIVE IN CREATING LOYALTY PROGRAM SATISFACTION AND STORE LOYALTY? AN EVIDENCE FROM INDONESIA RETAIL INDUSTRY - Hendrawan, Dimas; Anggraeni, Rila (Universitas Brawijaya, Indonesia, 2020)
Retailers must find specific ways to be able to continue to maintain their business with changes in consumer behavior. Some retailers use a loyalty program as their marketing strategy that provides certain additional benefits for frequent consumers. The objective of this work is to verify the effect of the loyalty program and loyalty program satisfaction on store loyalty. The data was collected through questionnaires from 150 respondents. The results reflected that loyalty programs significantly influence loyalty program satisfaction. Loyalty program satisfaction significantly influences store loyalty. The loyalty program is not directly related to storing loyalty. Loyalty program satisfaction mediates the effect of a loyalty program on store loyalty. The study highlights the importance of loyalty program satisfaction in the connection of loyalty program and store loyalty. To gain a loyal consumer, the retailer should improve the exclusivity and the attractiveness of the program. A useful and valuable reward will improve customer retention.